Analysis of the press coverage environmental risk of Mozambique: the Mozal Bypass case and newspaper “Notícias” and “O País” - Bussotti, L. (Revista Luciérnaga, 2013)
This article aims at verifying the way in which the Mozambican press covered the environmental risk caused by the activity of the multinational Mozal (Mozambique Aluminium). This company worked without filters, for 137 days, between 2010 and 2011, emitting polluting gases directly into the air (“Bypass”). The investigation intends to understand how the two main Mozambican daily newspapers, “Notícias” and “O País”, approached this issue. The methodology used has been quantitative (i.e. the number of articles edited and the sources used) as well as qualitative (i.e. content analysis, with the help of conceptual semantic maps) in nature. The theoretical basis of the research was the Social Amplification of Risk Framework (SARF). The investigation showed that the coverage, instead of clarifying the real environmental risks arising from the Bypass, was used for political leverage either in favour of or against the decisions of the Government.